Modeling and Control of Aeration in a Wastewater Treatment Plant - Larsson, Nils; Svensson, Daniel (My University, 2025)
In this thesis, several modified control strategies for aeration control in a wastewater treatment plant are implemented. Their performance with focus on energy consumption and airflow pattern is evaluated and compared to the existing control system. In the wastewater treatment process (WWTP), the biological step is where oxygen is needed to regulate the ammonium levels in the effluent water, which can therefore be controlled with the airflow. A model of a wastewater treatment plant (WWTP) was built in Simulink to simulate the plant and evaluate the different control strategies. Time periods for real-world data were selected and used, both for evaluation of the model accuracy and the control system performance. The final conclusions made are that there is room for improvement of the control system with for example feedforward of the inflow rate. However, improvements are limited to the daily variations and cannot help suppress the very high spikes in ammonia concentration seen a few times a year. The likely cause being that these are present due to capacity constraints being reached in the system. Energy consumption was also not substantially lowered by the modified control strategies and therefore, they are not recommended in their current form. Attempts were also made to implement an LQG controller. However, an LQG controller is based on a linear model of the system, and the WWTP is highly nonlinear with global stability concerns. Thus, an LQG controller was not feasible for this system.
Keywords: WWTP; modeling; control theory; ASM1; gain scheduling; LQG; feedforward; feedback